2020
DOI: 10.1108/etpc-05-2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

Cultural memory in English teaching: a critical autobiographical inquiry

Abstract: Purpose Contemporary standards-based reforms to teaching and teacher education are characterised by appeals to technical orientations to teacher professionalism. In addition, the standardisation agenda has targeted literacy education as a focus for interventions. This has highlighted an incongruence between standardised approaches to literacy and pedagogies and practices in subject English that have developed over time, and which represent disciplinary ways of knowing. Design/methodology/approach This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Literature [12] found that interleaved practice was more effective than closed practice learning in a study of 60 English language learners and that the development of working memory (WM) practice program enabled systematic form-centered speaking practice with examples of blocked English grammatical categories. Literature [13] introduces cultural memory as an explanatory educational experience to narrate the changes in EFL over time, and by finding the relationship between categorical memory strategies and vocabulary levels through memory rules, the efficiency of memorizing words will be increased, which will lead to the expansion of vocabulary. Literature [14] completed the design of an interactive practice platform for mobile teaching of English in open API universities through feedback elite teaching optimization algorithms, and this kind of English pedagogy effectively enhances the plasticity of students in English learning so that students can comfortably cope with the difficult problems in the English test questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature [12] found that interleaved practice was more effective than closed practice learning in a study of 60 English language learners and that the development of working memory (WM) practice program enabled systematic form-centered speaking practice with examples of blocked English grammatical categories. Literature [13] introduces cultural memory as an explanatory educational experience to narrate the changes in EFL over time, and by finding the relationship between categorical memory strategies and vocabulary levels through memory rules, the efficiency of memorizing words will be increased, which will lead to the expansion of vocabulary. Literature [14] completed the design of an interactive practice platform for mobile teaching of English in open API universities through feedback elite teaching optimization algorithms, and this kind of English pedagogy effectively enhances the plasticity of students in English learning so that students can comfortably cope with the difficult problems in the English test questions.…”
Section: Introductionmentioning
confidence: 99%
“…Fang Zhao, Mingxia Li and Cheng Feng. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] …”
mentioning
confidence: 99%